Hepatorenal syndrome from an ilio-iliac arteriovenous fistula: A rare complication from an endoleak - Giancarlo Speranza, BA, BS; Michael Pezold, MD, MS; Glenn Jacobowitz, MD; Karan Garg, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
Arteriovenous fistula is a rare and often unrecognized complication of aneurysms, with a varied and frequently inconsistent presentation. We present the case of an ilio-iliac arteriovenous fistula formation in a 71-year-old man associated with a type III endoleak after endovascular iliac branch repair. Because of rapidly progressing congestive heart failure and hepatorenal syndrome, we performed urgent endovascular repair with successful endoleak exclusion. After the procedure, the patient demonstrated a remarkably rapid and complete recovery.